Manufacturing of 3D printed laminated carbon fibre reinforced nylon composites: impact mechanics - Delporte, Yohan; Ghasemnejad, Hessam (Scientific Research Publishing, 2020)
This paper presents the manufacturing development of laminated Carbon Fibre Reinforced Thermoplastics Polymer (CFRTP) specimens, which show significant improvement of mechanical properties in comparison with existing thermoplastic composites. There is a need to improve structural performance of thermoplastic composites by using a fully integrated chopped and continuous carbon fibre bundle into a thermoplastic resin matrix in a laminated shape with various stacking sequences. The developed manufacturing technique is capable to print components with various fibre orientations, which is spotted as the novelty of this research. The CFRTP specimens were tested under quasi-static tensile and low-velocity impact loading to proof the improvement of mechanical performance in both static and dynamic applications. Our results indicate a significant improvement in impact resistance and energy absorption capability of CFRTP composites in comparison with existing thermoplastic composites.
Keywords: Additive; Nylon; CFRTP; Thermoplastic; Impact